Certain Aspects of Quantum Transport in Zigzag Graphene Nanoribbons - Pratap, Surender; Kumar, Sandeep; Singh, Ravi Pratap (Frontiers in Physics, 2022)
We have investigated the Fano factor and shot noise theoretically in the confined region of the potential well of zigzag graphene nanoribbon (ZGNR). We have found that the Fano factor is approximately 1, corresponding to the minimum conductivity (σ) for both symmetrical and asymmetrical potential wells. The conductivity plot with respect to Fermi energy appears as symmetrical plateaus on both sides of zero Fermi energy. Moreover, a peak observed at zero Fermi energy in the local density of states (LDOS) confirms the edge states in the system. The transmission properties of ZGNR in the confined region of the potential well are examined using the standard tight-binding Green’s function approach. The perfect transmission observed in the confined region of the potential well shows that pnp type transistor can be made with ZGNR [1, 2]. We have discussed the Fano factor, shot noise, conductivity and nanohub results in the continuation of previous results [3]. Our results show that the presence of van-Hove singularities in density of states (DOS) matters in the presence of edge states. The existence of these edge states is sensitive to the number of atoms considered and the nature of the potential wells. We have compared our numerical results with the results obtained from the nanohub software (CNTbands) of Purdue University [4].